PELAKSANAAN MANAJEMEN KEPALA PERPUSTAKAAN DALAM MENUNJANG KEBERHASILAN PELAYANAN INFORMASI DI DINAS PERPUSTAKAAN DAN ARSIP DAERAH KOTA JAMBI - Syamsuddin, Syamsuddin (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2017)
This writing aims to express the library manager responsibility as lead in library management through principles of library management. As we know that the information services process at Dinas Perpustakaan dan Arsip Daerah Kota Jambi faced some problems. The problems iclude information technology facilities ; incomplete information retrieval media ; the human resources which less be professional, and fund limitation. The problems are coused by the library manager doesn’t has librarianship knowledge and library management ; the library development program that didn’t has data to develop library in the next time ; the social relation among bad librarian. The problems can be solved by efforts through conduct the professional organizational coorporation ; support librarians to partcipate erudite activity ; increas fund ; evaluate the program which is not advantage ; use information technology facilities ; make information retrieval media not only manual but also automatic.